We refuse to forget : a true story of Black Creeks, American identity, and power - Gayle, Caleb (Riverhead Books, 2022)
"A landmark work of Black and Native American history that reconfigures our understanding of identity, race, and belonging and the inspiring ways marginalized people have pushed to redefine their world In this paradigm-shattering work of American history, Caleb Gayle tells the extraordinary story of the Creek Nation, a Native tribe that two centuries ago both owned slaves and accepted Black people as full members. Thanks to the leadership of a chief named Cow Tom--a Black former slave--a treaty with the U.S. government recognized Creek citizenship for its Black members. Yet this equality was shredded in the 1970s when Creek leaders revoked the citizenship of Black Creeks, even those who could trace their tribal history back generations. Why did this happen? What led to this reversal? How was the U.S. government involved? And how can marginalized people today defend themselves? These are some of the questions that award-winning journalist Caleb Gayle explores in this provocative examination of racial and ethnic identity. By delving deep into the historical record and interviewing Black Creeks suing the Creek Nation to have their citizenship reinstated, he lays bare the racism, ambition, and greed at the heart of this story. The result is an eye-opening account that challenges our preconceptions of identity as it shines new light on the long shadows of marginalization and white supremacy that continue to hamper progress for Black Americans"--